Pengaruh Fasilitas Terhadap Kepuasan Pengunjung di Objek Wisata Ngalau Indah Kota Payakumbuh - Farhan, Muhammad Shaquel; Meirina Chair, Ira (Jurnal Pendidikan Tambusai, 2021)
This study entitled The Effect of Facilities on Visitor Satisfaction at Ngalau Indah Tourism Object Payakumbuh City. The purpose of this study was to determine the effect of facilities on visitor satisfaction. The research was motivated by several problems regarding the facilities described by visitors who were in Ngalau Indah. The type of research used is descriptive quantitative with a causal associative approach. The type of sample in this study was to use purposive sampling technique so that 100 samples were obtained. The results of the research as a whole for the facility variable show a good category with an assessment percentage of 55% and for the visitor satisfaction variable it shows a very good category with an assessment percentage of 70%. Furthermore, the research results are based on: (1) the form of the facility indicator shows a good category with an interpretation of the percentage of respondents' assessment of 33%. (2) The facility function indicator shows a good category with an interpretation of the percentage of respondents' assessment of 34%. (3) The facility location indicator shows a good category with an interpretation of the response assessment percentage of respondents' assessment of 36%. And (4) the facility quality indicator shows a good category with an interpretation of the percentage of respondents' assessment of 33%. (5) the expectation indicator shows a good category with an interpretation of the percentage of respondents' assessment of 36%. (6) Performance indicators (performance) show a good category with the interpretation of the percentage of respondents' assessment of 31%. (7) The comparison indicator shows a very good category with an interpretation of the response assessment, the percentage of respondents' assessment is 78%. And (8) the confirmation indicator (confirmation) shows a good category with an interpretation of the percentage of respondents' assessment of 28%. (9) The discrepancy indicator shows a sufficient category with an interpretation of the response assessment, the percentage of respondents' assessment is 37%.